Rigorous morality: norms, values, and the comparative politics of human rights - Landman, Todd (John Hopkins University Press, 2016)
This paper argues that there is a strong role for empirical analysis to be used to address fundamental normative questions. Using human rights as an example, the article shows that the evolution of the international regime of human rights provides a standard against which country level performance can be both judged and explained through the application of empirical approaches in comparative politics. It argues further that different kinds of human rights measures (events, standards, surveys, and official statistics) and comparative methods (large-N, small-N and single-country studies) offer systematic ways in which to map, explain, and understand the variation in human rights abuse around the world. In this way, the comparative politics of human rights is prime example of how the ‘is’ of the world can be used to address the ‘ought’ of international human rights theory, philosophy, and law. The example of human rights analysis in comparative politics shows a strong role for value- based and problem-based research that remains systematic in its approach while at the same producing outputs that are of public value.